I.i.3.a Minutes, - Labour Party (Ireland) (1971)
Minutes of the Administrative Council which took place on 10 Feb 1971 principally concerning: decimalisation; allegations of manipulation of voting at the special delegate conference 1970; discussion of draft annual report; western development policy; proposed Administrative Council motions to Party Conference. Meeting chaired by Michael Higgins. Minutes signed by, Roddy Connolly, Party Chair, and Brendan Halligan, General Secretary. Also includes memorandum to the Conference Arrangements Committee and Administrative Council prepared by Dermot Boucher, Standing Orders Committee, alleging voting manipulation and the special delegate conference 1970 in Cork, County Cork. (11 pp)